Smuggling Across the Windsor-Detroit Border: Folk Art, Sexual Difference and Cultural Identity - Langlois, Janet (Ethnologies, 1991)
Acts of border smuggling, and the stories about them, are folk art for they reveal culturally-shared strategies for moving goods from one country to the other and for duping Customs officiais in the process. Yet they are more. A case is made here through the micro-analysis of family smuggling across the “Windsor-Detroit Funnel” that gender differences revealed in smuggling strategies ultimately articulate complex problems in border relations and cultural identity.